Revolution from below: The rise of local politics and the fall of Bolivia's party system - Jean-Paul Faguet (London School of Economics and Political Science (LSE), Department of International Development, 2017)
For 50 years Bolivia's political party system was a surprisingly robust component of an otherwise fragile democracy. How did a gas pipeline dispute spark a revolution that overturned the political system, destroyed existing political parties, and re-cast the relationship between state and society? I examine how the arrival of local government shifted the nation's politics from a typical 20th century, left-right axis of competition deeply unsuited to a society like Bolivia, to an ethnic and cultural axis more closely aligned with its major social cleavage. This shift made elite parties redundant, and transformed the country's politics by facilitating the rise of structurally distinct political organizations, and a new indigenous political class. Decentralization was the trigger - not the cause - that made Bolivia's latent cleavage political, sparking revolution from below. I suggest a folk theorem of identitarian cleavage, and outline a mechanism linking deep social cleavage to sudden political change.
Keywords: 330; Cleavage theory; political parties; elite politics; decentralization; Latin America; Bolivia